DAMPAK PENGURANGAN RUANG TERBUKA HIJAU (RTH) PERKOTAAN TERHADAP PENINGKATAN SUHU UDARA DENGAN METODE PENGINDERAAN JAUH (IMPACT REDUCING URBAN GREEN SPACE TOWARDS INCREASING AIR TEMPERATURE USING LANDSAT DATA) - Sobri Effendy (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2009)
The aim of this study is to determine correlation urban green space and air temperature using landsat data at JABOTABEK. Using Landsat data can cover deficit data from conventional climate station also can to identify magnitude urban green space. Air temperature series are derived from band 6 images Landsat data, including the NDVI from band 3 and 4 which is used as the bases for generating urban green space of the study area. The correlation urban green space and air temperature are non-linier correlation to entire all locations Jakarta, Bogor city and regency, also Tangerang and Bekasi. Reduction or increasing urban green space causes enhanced or depreciation air temperature with differ magnitude, where every decreased 50% urban green space area causes increase air temperature up 0.4 to 1.8oC, while the increase 50 % of urban green space area only decrease air temperature as big as up 0.2 to 0.5oC. This result that important meaning to defend urban green space reduction, also using Landsat data can equip climate data deficit from conventional climate station.